Upaya Meningkatkan Fisik Motorik Kasar Anak Usia 5-6 Tahun Melalui Permainan Jump Zig Zag - Noor Siamah; Rizki Amalia; Joni Joni (Jurnal Pendidikan Tuntas, 2024)
This research was motivated by the low gross motor skills of children aged 5-6 years at the TK Dharma Wanita , Kampar Regency. For this reason, a concrete application is needed to be able to find the right way regarding children's gross motor skills, namely the application of the Jump Zig Zag game. This research aims to find out whether the application of the Jump Zig Zag game can improve gross motor skills in children aged 5-6 years at the TK Dharma Wanita , Kampar Regency. This type of research is classroom action research which is an examination of learning activities in the form of actions, which are deliberately created and occur in a class together with a total of 16 children consisting of 8 boys and 8 girls. . Data collection techniques for data collection in this research are observation and documentation. The data analysis technique used in this research is the percentage technique. From the results of classroom action research and discussions as described, the conclusion regarding the results of this research is that using the Jump Zig Zag game can improve the gross motor skills of children aged 5-6 years at TK Dharma Wanita , Kampar Regency. Keywords: Zig Zag Jump Game, Gross Motor, Aged 5-6 Years.